Left Atrial Dissection Induced by Coronary Sinus Catheter-Related Injury - Zhanru Qi, MM; Fang Xu, MD; Mingxia Li, MD; Xuan Luo, MD; Zheyan Wang, MD; Xiaoxian Wang, MM; Beibei Ge, MM; Dongjin Wang, MD; Jing Yao, MD (JACC: Case Reports, 2024)
We present a unique case of left atrial (LA) dissection in a 46-year-old man following aortic dissection surgery. The LA dissection was attributed to coronary sinus catheter–related injury. This report highlights the importance of recognizing this rare complication and the crucial role of transesophageal echocardiography in its diagnosis. We discuss the pathogenesis, diagnostic criteria, and management strategies for LA dissection.